The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jtcvs.2014.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Novel technique for delayed sternal closure: Soft tissue approximation with substernal bridge

Abstract: References1. Alsoufi B, Rao V, Borger MA, Maganti M, Armstrong S, Feindel CM, et al. Shortand long-term results of triple valve surgery in the modern era. Ann Thorac Surg. 2006;81:2172-8. 2. Cohn LH, Adams DH, Couper GS, Bichell DP, Rosborough DM, Sears SP, et al. Minimally invasive cardiac valve surgery improves patient satisfaction while reducing costs of cardiac valve replacement and repair. Ann Surg. 1997; 226:421-8. 3. Gammie JS, Zhao Y, Peterson ED, O'Brien SM, Rankin JS, Griffith BPJ.Less-invasive mitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(4 reference statements)
0
3
0
Order By: Relevance
“… 1 Other studies have shown good results with sewing a substernal pericardial patch combined with soft tissue closure. 2 Our approach, involving a bridging plate along with skin reapproximation, is unique, and we believe further evaluation in the form of a multicenter study might be of value. Although little is known about infection risk with different techniques, a biologic barrier affords the lowest risk theoretically because it allows the patients immune system to protect the wound.…”
Section: Commentmentioning
confidence: 96%
“… 1 Other studies have shown good results with sewing a substernal pericardial patch combined with soft tissue closure. 2 Our approach, involving a bridging plate along with skin reapproximation, is unique, and we believe further evaluation in the form of a multicenter study might be of value. Although little is known about infection risk with different techniques, a biologic barrier affords the lowest risk theoretically because it allows the patients immune system to protect the wound.…”
Section: Commentmentioning
confidence: 96%
“…A similar approach to DSC was published in The Journal of Thoracic and Cardiovascular Surgery in 2014, with similarly small sample size and low infection rates. 9 Balasubramanian and Bhama 8 demonstrate that this approach to DSC is feasible and safe, but the impact on A randomized study is required to determine whether closing the skin and soft tissues over an open sternum reduces the risk of sternal wound infection in these critically ill cardiac surgery patients.…”
mentioning
confidence: 99%
“…A similar approach to DSC was published in The Journal of Thoracic and Cardiovascular Surgery in 2014, with similarly small sample size and low infection rates. 9 …”
mentioning
confidence: 99%